Comparative efficiency of silica gel, biochar, and plant growth promoting bacteria on Cr and Pb availability to Solanum melongena L. in contaminated soil irrigated with wastewater - Rabiya, Umm e; Ali, Muhammad; Farooq, Muhammad Ansar; Siddiq, Zafar; Alamri, Saud A.; Siddiqui, Manzer H.; Khan, Waqas-ud-Din (Frontiers in Plant Science, 2022)
Crop irrigation with untreated wastewater is a routine practice in developing countries that causes multiple human health consequences. A comparative study was performed to evaluate the efficiency of chitosan polymerized silica gel (CP-silica gel), zinc enriched biochar (ZnBc) and three bacterial species such as Trichococcus sp (B1), Pseudomonas alcaligenes (B2) and Bacillus subtilis (B3) to regulate total Cr and Pb stress in soil and Solanum melongena L. plant. Initially, a biosorption trial was conducted to test the heavy metal removal efficiency of three bacterial species B1, B2 and B3. Among three bacterial isolates, B3 showed maximum total Cr and Pb removal efficiency. Then, a pot study was conducted with 12 different treatments having three replicates. After harvesting, different growth and biochemical parameters such as chlorophyll concentration, protein, phenolics, reactive oxygen species and antioxidant enzymes were analyzed. The results demonstrated that wastewater application significantly (p ≤ 0.01) reduced the fresh and dry weights of root, stem and leaves due to high total Cr and Pb toxicity. However, CP-silica gel and ZnBc treatments performed best when applied in combination with B3. The concentration of leaf total Cr was significantly decreased (91 and 85 %) with application of ZnBc + B3 and CP-Silica gel + B3, respectively, as compared to control. There was a reduction in stem hydrogen peroxide (87%) and malondialdehyde (81%) recorded with CP-silica gel + B3 treatment due to enhanced activities of antioxidant enzymes viz. ascorbate peroxidase (6-folds) and catalase (7-folds) relative to control. Similarly, leaf total phenolics (3-folds) and protein (6-folds) contents were enhanced with CP silica gel+B3 application relative to control. Overall, CP-silica gel and ZnBc with B3 application proved to be the most appropriate treatments and can be used in developing countries to limit the deleterious effects of total Cr and Pb pollution.